Risky behaviors and educational attainment among young Mexican-origin mothers: The role of acculturative stress and the educational aspiration–expectation gap. (May 2016) - Bravo, Diamond Y.; Umaña-Taylor, Adriana J.; Toomey, Russell B.; Updegraff, Kimberly A.; Jahromi, Laudan B.
Abstract: The current longitudinal study examined how Mexican-origin adolescent mothers' ( N = 204) reports of acculturative stress during late adolescence were associated with their educational attainment and engagement in risky behaviors in young adulthood, 4 years post-partum; we also examined whether this association was mediated by discrepancies between adolescents' educational aspirations and expectations. Findings revealed that mothers' greater reports of stress regarding English competency pressures and pressures to assimilate were associated with a larger gap between their aspirations and expectations. Mothers' reports of greater stress from pressures against assimilation, however, were associated with a smaller gap between aspirations and expectations. As expected, a larger gap between aspirations and expectations was associated with lower educational attainment and increased engagement in risky behaviors. Finally, significant mediation emerged, suggesting that the influence of stress from English competency pressures and pressures to assimilate on young mothers' educational attainment and engagement in risky behaviors was mediated through the aspiration–expectation gap. Findings are discussed with respect to understanding discrepancies between young mothers' aspirations and expectations in the context of acculturative stress.